Examining Muscle Activity Differences During Single and Dual Vector Elastic Resistance Exercises - Ryan WG Bench; Sydney E Thompson; Alan C Cudlip; Michael WR Holmes (North American Sports Medicine Institute, 2021)
# Background Elastic resistance exercise is a common part of rehabilitation programs. While these exercises are highly prevalent, little information exists on how adding an additional resistance vector with a different direction from the primary vector alters muscle activity of the upper extremity. # Purpose The purpose of this study was to examine the effects of dual vector exercises on torso and upper extremity muscle activity in comparison to traditional single vector techniques. # Study Design Repeated measures design. # Methods Sixteen healthy university-aged males completed four common shoulder exercises against elastic resistance (abduction, flexion, internal rotation, external rotation) while using a single or dual elastic vector at a fixed cadence and standardized elastic elongation. Surface electromyography was collected from 16 muscles of the right upper extremity. Mean, peak and integrated activity were extracted from linear enveloped and normalized data and a 2-way repeated measures ANOVA examined differences between conditions. # Results All independent variables differentially influenced activation. Interactions between single/dual vectors and exercise type affected mean activation in 11/16 muscles, while interactions in peak activation existed in 7/16 muscles. Adding a secondary vector increased activation predominantly in flexion or abduction exercises; little changes existed when adding a second vector in internal and external rotation exercises. The dual vector exercise in abduction significantly increased mean activation in lower trapezius by 25.6 ± 8.11 %MVC and peak activation in supraspinatus by 29.4 ± 5.94 %MVC (p<0.01). Interactions between single/dual vectors and exercise type affected integrated electromyography for most muscles; the majority of these muscles had the highest integrated electromyography in the dual vector abduction condition. # Conclusion Muscle activity often increased with a second resistance vector added; however, the magnitude was exercise-dependent. The majority of these changes existed in the flexion and abduction exercises, with little differences in the internal or external rotation exercises. # Level of Evidence 3b